2004
DOI: 10.1159/000080843
|View full text |Cite
|
Sign up to set email alerts
|

Localized Primary Amyloidosis of the Genitourinary Tract: Does Conservatism Help?

Abstract: Primary amyloidosis of the genitourinary tract is a rare clinical entity with an excellent prognosis in most cases. It is of interest to the urologist as it mimics malignancy. The definitive diagnosis is made on histologic examination and by excluding secondary causes of amyloidosis. We present 4 patients with primary localized amyloidosis of the genitourinary tract who were treated with transurethral resections alone with satisfactory outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Typically, in localized amyloidosis of the bladder, amyloid deposits are demonstrated in the lamina propria and muscular is propria with vessel wall involvement. Similar findings were also seen in our patient (8). Some studies have found anti-inflammatory agents such as oral colchicine to be beneficial in the focal bladder amyloidosis while diffuse or locally extensive bladder involvement usually requires conventional transurethral resection that should be supplemented with intravesical dimethyl sulfoxide (DMSO) instillation with periodic cystoscopy (9, 10).…”
Section: Discussionsupporting
confidence: 92%
“…Typically, in localized amyloidosis of the bladder, amyloid deposits are demonstrated in the lamina propria and muscular is propria with vessel wall involvement. Similar findings were also seen in our patient (8). Some studies have found anti-inflammatory agents such as oral colchicine to be beneficial in the focal bladder amyloidosis while diffuse or locally extensive bladder involvement usually requires conventional transurethral resection that should be supplemented with intravesical dimethyl sulfoxide (DMSO) instillation with periodic cystoscopy (9, 10).…”
Section: Discussionsupporting
confidence: 92%
“… 9 In another series, four patients with bladder amyloidosis treated with transurethral resection alone achieved a satisfactory outcome. 11 Thus, DMSO perfusion is not as important as once thought.…”
Section: Discussionmentioning
confidence: 97%
“…Management of primary amyloidosis is mainly TURBT with symptomatic therapy if it is localized. [4] Adjuvant intravesical dimethyl sulfoxide therapy has been useful in selected patients with intractable hematuria. [5] However, follow up periodic cystoscopy is mandatory.…”
Section: Discussionmentioning
confidence: 99%